In the Name of the Public: An Ethnographic Approach to the Tastes and Habits of Film Audiences - Azcona, M. Mar; Luzón, Virginia; Tarancón, Juan (Miscelánea: A Journal of English and American Studies, 2005)
Until very recently audience research was a neglected area in film studies. Critics tended to take for granted that they could read the minds of the implied spectator(s). However, cultural studies paved the way for a serious consideration of individual spectators’ actual readings. This paper, which is the continuation of a previous study, seeks to foreground the opinions of real spectators in our particular geographical context. In our previous and current investigation we made use of sociological research methods in order to obtain reliable data about cinema habits and tastes. This paper presents the results obtained through a self administered questionnaire distributed over a four-month period among three different age groups of the population of Zaragoza